Isham White, The Laws and Ordinances of the City of Denver, Colorado 355, § 14 (1886) - (:unkn) unknown (My University, 1886)
Prohibited any wagon, dray, cart, or other vehicle loaded in whole or in part with gun powder or gun-cotton in any street, alleyway, highway, or place in the city. All vehicles transporting powder shall have the word "Powder" painted upon the sides in large letters.
Keywords: GUNPOWDER - TRANSPORTATION